1995
DOI: 10.1006/cbir.1995.1045
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human Caco‐2 intestinal epithelial cell phenotype by protein kinase C inhibitors

Abstract: Protein kinase C (PKC) isoforms are altered in colon tumors and upon exposure of intestinal mucosa to nutrients. We evaluated the effects of the PKC inhibitors staurosporine and calphostin C on human Caco-2 intestinal epithelial proliferation, motility, and differentiation. Motility was quantitated by monolayer expansion and the brush border enzymes dipeptidyl dipeptidase (DPDD) and alkaline phosphatase (AP) by synthetic substrate digestion. Staurosporine (0.03-1.0 ng/ml) and calphostin C (10(-12) M-10(-4) M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…After first light-activating the calphostin C as previously described (7,34), we pretreated serum-starved Caco-2 cells with 10 nM calphostin C for 3 h before initiation of cyclic strain. We have previously shown that calphostin C treatment in this manner ablates strainstimulated PKC activity (6,7,34).…”
Section: Methodsmentioning
confidence: 86%
“…After first light-activating the calphostin C as previously described (7,34), we pretreated serum-starved Caco-2 cells with 10 nM calphostin C for 3 h before initiation of cyclic strain. We have previously shown that calphostin C treatment in this manner ablates strainstimulated PKC activity (6,7,34).…”
Section: Methodsmentioning
confidence: 86%
“…However, some observations suggest that activation of PKC is associated with intestinal and/or colonic cell proliferation, whereas PKC inhibition and translocation of the PKA catalytic subunit in the nucleus are associated with Caco‐2 cell differentiation (Craven and De Rubertis, 1987; Pignata et al, 1994). Interestingly, staurosporine has been shown to have hormesis‐like stimulatory and inhibitory effects on dipeptidyl dipeptidase and alkaline phosphatase activities, respectively, two differentiation markers in Caco‐2 cells (Basson and Hong, 1995). In the same study, staurosporine also decreased cell proliferation but still stimulated dipeptidyl dipeptidase activity in the presence of DNA synthesis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin is a nuclear target protein for cyclic AMP and protein kinase C. Cyclic AMPdependent protein kinase influences the phosphorylation of nucleolin. According to Basson and Hong (1995), protein kinase C may regulate intestinal epithelial differentiation. Activation of Ca 2+ -dependent protein kinase C can cause a reduction in proliferation, while increasing apoptosis and differentiation in CaCo-2 cells (Chen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%